EVALUASI KINERJA KEUANGAN SELAMA PANDEMI COVID 19 PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020–2023 - Theresa Yuliana Jaeng; Wihelmina Maryetha Yulia Jaeng (Universitas Nusa Nipa Maumere, 2025)
This study aims to analyze the financial performance of five food and beverage subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period using financial ratios. The analyzed ratios include liquidity (Current Ratio), profitability (ROA, ROE, NPM), solvency (DAR, DER), and activity (TATO, FATO). The data were obtained from officially published annual financial reports. The results of the analysis show that PT Delta Djakarta Tbk demonstrated the most balanced performance, with strong liquidity, profitability, and solvency. In contrast, PT Sariguna Primatirta Tbk, despite showing high efficiency in fixed asset utilization, exhibited high leverage and low profitability. The findings of this study can serve as a basis for strategic decision-making for both investors and company management.